Overview of the Literature on the Impact of Food Price Volatility - Hariz Eko Wibowo; Ridha Rizki Novanda; Rihan Ifebri; Ariffatchur Fauzi (Badan Penerbitan Fakultas Pertanian (BPFP), 2023)
Increased price volatility can increase investment risk and, at the same time, reduce investment. Food price volatility will have different effects on surplus and deficit households. Instead of investing, uncertainty in food prices can be a significant barrier for many deficit households to escape poverty. On the other hand, surplus households can save. Agricultural price shocks and volatility threaten the poorest people's access to food and economic welfare. The detrimental welfare impact on the consumers outweighs the gains to producers increasing the number of poor and in the depth of poverty. Decreased income in already low-income countries might result in malnutrition, death, and withdrawal of children from education. There is a substantial correlation between a country's food production index, poverty level, degree of urbanization and the risk that it will experience food riots, given the empirical evidence that shocks to agricultural prices can spark civil unrest and wars, as well as the devastating effects that civil wars and other forms of violence have on economic growth.